Effect of mineral filler on low velocity impact behaviour of bi-directional glass fibre/epoxy composites exposed to varied temperature conditions - K.S Lokesh; C G Ramachandra; Shrinivasa Mayya.D; T Varuna; Praveen Kumar Kanti; Abhinav Kumar; Melkamu Biyana Regasa (PLoS ONE, 2025)
Fibre reinforced plastics are predominantly used in automotive, aerospace applications due to their promising features of low cost, easy of processing and durability, however these composites are more susceptible to varied temperature conditions under different loading conditions. One such problem where these composites vary greatly in their performance is due to impact loading conditions. The objective of present research is to determine the effect of calcium inosilicate (also termed as wollastonite) powder which is used as a filler on low velocity impact (LVI) behaviour of bi-directional glass fibre reinforced with epoxy thermosets (GFRP) for different loading percentage of 1%,3%,5% and 7%. Composites were prepared through manual lay-up route and prepared samples were exposed for 3 different temperature conditions of continuous heating and cooling cycles at +500c, −50C including room temperature conditions for 168hrs. Aged samples were tested for low velocity impact(LVI) testing by keeping constant energy of 30J. Results revealed that addition up to 3% filler influence largely on LVI response of GFRP composites for all the temperature conditions, addition to this polynomial regression of 9th order was performed and the results were best fit with experimental values. Fractography study revealed the severity of damage modes upon LVI testing.